In situ XPS investigations of Cu1-xNixZnAl-mixed metal oxide catalysts used in the oxidative steam reforming of bio-ethanol - Velu, S.; Suzuki, K.; Vijayaraj, M.; Barman, S.; Gopinath, Chinnakonda S. (Applied Catalysis B - Environmental, 2005)
A series of CuNiZnAl-multicomponent mixed metal oxide catalysts with various Cu/Ni ratios were prepared by the thermal decomposition of Cu1-xNixZnAl-hydrotalcite-like precursors and tested for oxidative steam reforming of bio-ethanol. Dehydrogenation of EtOH to CH3CHO is favored by Cu-rich catalyst. Introduction of Ni leads to C-C bond rupture and producing CO, CO2 and CH4. H-2 yield (selectivity) varied between 2.6-3.0 mol/mol of ethanol converted (50-55%) for all catalysts at 300 degreesC. The above catalysts were subjected to in situ XPS studies to understand the nature of active species involved in the catalytic reaction. Core level and valence band XPS as well as Auger electron spectroscopy revealed the existence of Cu2+, Ni2+ and Zn2+ ions on calcined materials. Upon in situ reduction at reactions temperatures, the Cu2+ was fully reduced to Cu-0. while Ni2+ and Zn2+ were partially reduced to Ni-0 and Zn-0, respectively. On reduction, the nature of ZnO on Cu-rich catalyst changes from crystalline to amorphous, relatively inert and highly stabilized electronically. Relative concentration of the Ni-0 and Zn-0 increases upon reduction with decreasing Cu-content. Valence band results demonstrated that the overlap between 3d bands of Cu and Ni was marginal on calcined materials, and no overlap due to metallic clusters formation after reduction. Nonetheless, the density of states at Fermi level increases dramatically for Ni-rich catalysts and likely this influences the product selectivity. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: auger electron spectroscopy; Autothermal reforming; Bio-ethanol; copper oxide; fuel cell; Hydrogen; hydrotalcite; mixed metal oxides; nickel oxide; oxidative steam reforming; Steam reforming; XPS

On the ``Active spacer and stabilizer'' role of Zn in Cu1-xZnxFe2O4 in the selective mono-N-methylation of aniline: XPS and catalysis study - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Journal of Catalysis, 2006)
A systematic catalytic methylation study on ferrospinel materials led to the selective production of N-methylaniline (NMA) with Cu1-xZnxFe2O4. Aniline methylation was carried out on Cu1-xZnxFe2O4 with a feed composition of CH3OH:PhNH2:H2O = 3:1:1 at 513-633 K. NMA was formed selectively on all of the catalyst compositions, with trace amounts of secondary products under most of the conditions. Cu0.5Zn0.5Fe2O4 composition showed high catalytic activity and stability up to 100 h. Although the Cu2+ was responsible for methylation activity, Zn2+ enhanced the overall stability of the catalyst system. XPS investigations revealed that the degree of Cu2+ reduction decreased dramatically from x = 0.05/0.25 to 0.5/0.75 on spent catalysts. TPR studies indicated that the reducibility of Cu2+ decreased from fully reducible at 523 K with Cu-rich compositions to partially reducible at 573 K on x = 0.5. Stable activity observed on Cu0.5Zn0.5Fe2O4 can be attributed to the highly heterogeneous distribution of metal ions. This heterogeneous distribution indicates an important role of zinc, likely as an ``active spacer cum stabilizee' that hinders the reduction of active Cu2+ and contributes to prolonged activity. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Aniline; Ferrite; N-methylaniline; N-methylation; spacer; stabilizer; surface distribution; TPR; XPS

Effect of spacer groups on the performance of MCM-41-supported platinum cluster-derived hydrogenation catalysts - Maity, Niladri; Basu, Susmit; Mapa, Maitri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
MCM-41 was functionalized with (EtO)(3)SiCH2Cl, (MeO)(3)SiCH2CH2CH2Cl, and (CH3)Cl2SiCH2Cl. The functionalized materials were characterized by solid-state NMR (CPMAS, Si-29 and C-13) and XPS. The NMR data indicate that three new silicon environments were created by(EtO)(3)SiCH2Cl and (MeO)(3)SiCH2CH2CH2Cl, whereas with (CH3)Cl2SiCH2Cl, two new silicon environments were obtained. XPS results from Si 2p core level and the valence band from the material functionalized by (MeO)(3)Si(CH2)(3)Cl was found to be the same as that of the corresponding fresh catalyst (1a), in contrast to that of the materials functionalized by the other two silane reagents. After further functionalization with triethylamine, these materials were used as inorganic anion exchangers to support the cluster anion [Pt-12(CO)(24)](2-). Solid-state NMR (29Si, C-13, N-15) was used to establish the presence of the quaternary ammonium group in the cluster-supported species. Analogous materials were also created using fumed silica as the support, and all of the cluster-supported materials were tested as catalysts for the hydrogenation of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, ethylacetoacetate, 4-nitrotoluene, cyclohexanone, allyl alcohol, and styrene. The best activity was obtained for the catalyst that had MCM-41 as the support and chloropropyl as the spacer group. TEM showed that the supports and the spacer groups had observable effects on the platinum crystallite size of the catalysts. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: functionalized inorganic oxides; hydrogenation catalysts; MCM-41; platinum carbonyl cluster; Solid-state NMR; spacer groups; XPS

Selective production of methoxyphenols from dihydroxybenzenes on alkali metal ion-loaded MgO - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Journal of Catalysis, 2006)
Selective O-methylation of dihydroxybenzenes (DHBs; catechol, resorcinol, and hydroquinone) to methoxyphenols (MPs) was carried out with dimethylcarbonate on MgO and alkali metal ion (Li, K, and Cs)-loaded MgO between 523 and 603 K. Catalytic activity and product selectivity varied with respect to DHB substrates. Selectivity for O-methylated products increased with increasing basicity of alkali ions; however, K-MgO showed high and stable activity toward MPs. Selectivity for MPs obtained from three substrates increased in the following order: catechol < resorcinol < hydroquinone. The mode of interaction of substrates on the catalysts surface influenced reactivity and product selectivity. It is likely that the low reaction temperatures used (< 603 K) kinetically control and favor high MP selectivity from DHBs. Calcined and spent catalysts were characterized by XRD, surface area, SEM, thermal analysis, NMR, and XPS. XRD analysis revealed the formation of alkali oxide phases on alkali-loaded MgO. Crystallite size and surface area of the catalysts decreased after methylation reactions, except on K-MgO. TGA showed 4060 wt% coke deposition on spent catalysts. TGA in N-2 followed by air and C-13 CP-MAS NMR measurements indicated the nature of deposited carbon to be molecular species, graphite, MgCO3 and polyaromatics. XPS revealed the nature and availability of active sites on the spent catalysts, as well as the same changes with reaction conditions and correlated with catalytic activity. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: alkali-loaded MgO; dihydroxybenzene; K-MgO; methoxyphenol; MgO; O-methylation; thermal analysis; XPS

Electronic structure evolution of Pd@Co nanocatalysts under oxidation and reduction conditions and preferential CO oxidation - Jain, Ruchi; Gopinath, Chinnakonda S. (ChemCatChem, 2020)
Herein, we present the surface electronic structure and morphological evolution under reduction and oxidation conditions for Pd@Co (PC) core-shell nanoparticles with different Pd : Co ratio (PC=2 : 1, 1 : 1 and 1 : 2). Extensive measurements have been made with NAPXPS (near ambient pressure x-ray photoelectron spectroscopy) under oxidising and reducing conditions, and ex-situ HRTEM. It has been demonstrated that PC catalysts are thermally stable towards morphological changes, at least up to 575 K. Nonetheless, it shows a significant surface electronic structure changes under reaction environments, which are highly relevant to heterogeneous catalysis. As expected, high (low) population of metallic (oxidised) Co was observed, while retaining core shell structure under reduction (H(2)and vacuum annealing) environment. Interestingly, the Pd-Co metallic interface helps to overcome the pyrophoric nature of cobalt and stabilised a significant amount of metallic Co at Pd-Co interface even in the presence of 0.1 mbar O(2)up to 575 K. The presence of Pd-Co and Pd-Co@Co(3)O(4)interfaces in reaction environment makes the catalyst dual functional. The proof of concept has been explored in terms of oxidation of CO in the presence of H(2)or O-2.
Keywords: Core-Shell morphology; Electronic Structure; heterogeneous catalysis; interface; XPS